Identification and epidemiological analysis of a putative novel hantavirus in Australian flying foxes - Craig S. Smith; Darren J. Underwood; Anita Gordon; Michael J. Pyne; Anna Smyth; Benjamin Genge; Luke Driver; David G. Mayer; Jane Oakey (Virus Genes, 2025)
In July 2017, an investigation into the cause of neurological signs in a black flying fox ( Pteropus alecto , family Pteropodidae ) identified a putative novel hantavirus (Robina virus, ROBV, order Bunyavirales , family Hantaviridae , genus Mobatvirus ) in its brain. Analysis of the evolutionary relationship between other hantaviruses using maximum-likelihood, a systematic Bayesian clustering approach, and a minimum spanning tree, all suggest that ROBV is most closely related to another Mobatvirus , Quezon virus, previously identified in the lung of a Philippine frugivorous bat ( Rousettus amplexicaudatus , also family Pteropodidae ). Subsequently, between March 2018 and October 2023, a total of 495 bats were opportunistically screened for ROBV with an experimental qRT-PCR. The total prevalence of ROBV RNA detected in Pteropus spp. was 4.2% (95% CI 2.8–6.4%). Binomial modelling identified that there was substantial evidence supporting an increase ( P = 0.033) in the detection of ROBV RNA in bats in 2019 and 2020 suggesting of a possible transient epidemic. There was also moderate evidence to support the effect of season ( P = 0.064), with peak detection in the cooler seasons, autumn, and winter, possibly driven by physiological and ecological factors similar to those already identified for other bat-borne viruses. This is Australia’s first reported putative hantavirus and its identification could expand the southern known range of hantaviruses in Australasia.